2010
DOI: 10.1590/s0103-50532010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical removal of CuII in the presence of humic acid

Abstract: ) was studied at different current densities (30-80 mA cm -2 ) using a filter-press cell, Ti/Ru 0.3 Ti 0.7 O 2 anode and stainless steel cathode. The electrolyses were performed with and without membrane separating the cell compartments [(homogeneous anionic (Nafion R117), heterogeneous cationic (Ionac MC-3470) and heterogeneous anionic (Ionac MA-3475)]. The influence of the membrane on the rate of Cu II removal was bigger for cationic membranes. Current efficiencies up to ca. 55% (Ionac MC-3470) for Cu II rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The removal efficiency (R%) and the quantity of metal ions adsorbed per gram of adsorbent was calculated using eqn (1) and (2). All experiments were carried out at 20 C except the temperature experiments.…”
Section: Adsorption Kinetics and Equilibrium Isotherm Of Metal Ions Omentioning
confidence: 99%
See 1 more Smart Citation
“…The removal efficiency (R%) and the quantity of metal ions adsorbed per gram of adsorbent was calculated using eqn (1) and (2). All experiments were carried out at 20 C except the temperature experiments.…”
Section: Adsorption Kinetics and Equilibrium Isotherm Of Metal Ions Omentioning
confidence: 99%
“…[1][2][3][4] Among these methods, adsorption is generally preferred due to its high efficiency, ease of handling and availability of different sorbents. Various methods have been developed for the heavy metals removal such as solvent extraction, membrane separation, precipitation, reduction, electrochemical treatment, adsorption, occulation, reverse osmosis and ion exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with the obtained results without the membrane it can be seen that there is a decrease of 17.6% in the color removal at 1.8 V and 13% at 2.2 V. Again, it is observed that the best color removal was obtained at 2.2 V. These results indicate that the use of a membrane is capable of reducing the formation of ClO − as seen in previous papers. 41 The E EO values with and without the membrane are given in Figure 9.…”
Section: Influence Of Nacl Concentration and Applied Potentialmentioning
confidence: 99%
“…Comparing with the obtained results without the membrane it can be seen that there is a decrease of 17.6% in the color removal at 1.8 V and 13% at 2.2 V. Again, it is observed that the best color removal was obtained at 2.2 V. These results indicate that the use of a membrane is capable of reducing the formation of ClO − as seen in previous papers. 41 The E EO values with and without the membrane are given in Figure 9.Total organic carbon (TOC) is a very important parameter applied to wastewater pollution analyses. 42 For the degradation of RO16 TOC removal was analyzed as function of potential applied, NaCl concentrations and use of a membrane.…”
mentioning
confidence: 99%
“…The first is the indirect electrochemical degradation of various polluting substances using oxide electrodes (typically mixtures of RuO 2 and TiO 2 ) for the in situ generation of Cl 2 . The matrices investigated include pesticides such as atrazine [4] and carbaryl [5]; real textile waste [6,7] and Cu(II)-humic acid complexes [8]. It was noticed that significant efficiencies are obtained when in situ generated chlorine is used.…”
Section: Introductionmentioning
confidence: 99%